Gender dimorphism in parasitic behavioural manipulation hypothesis - Abdulai-Saiku, Samira (2017)
The behavioural manipulation hypothesis states that a parasite will alter those parts of its host behaviour important to its survival and transmission in order to increase its fitness. It has been demonstrated that there is a gender dimorphism in parasitic infections in many hosts. This raises an important question of the role of gender in parasitic behavioural manipulation. On the one hand, it is possible that gender dimorphism in parasite infection and prevalence extends to parasitic behavioural manipulation. In this case, manipulation will only occur in the gender that is preferentially infected. On the other hand, there is a possibility that gender dimorphism occurs on the level of the mechanism of manipulation rather than on phenotypic expression of manipulated trait. The aim of my thesis is to explore the possibilities presented by both options using the protozoan parasite Toxoplasma gondii as a model. I first demonstrate that Toxoplasma is able to alter behavioural response of female rats to cat odour. This is similar to the response that has previously been observed in male rats. I further demonstrate that this behaviour change is not as a result of masculinization of infected female rats by showing no change in plasma testosterone and arginine vasopressin (AVP) transcript levels in the posterior dorsal medial amygdala (MeApd). These are both substrates reported to drive the same behaviour in male rats. Alternatively, I propose a role for the oxytocin system in the MeApd which has an innate gender dimorphic expression and function. Based on my findings, I propose that manipulation by Toxoplasma gondii does not occur at the level of the substrates that are implicated in the mechanism. Rather I propose manipulation affects the negotiation of the approach-avoidance conflict which is an important part of all aspects of social behaviour. Innate social behavioural responses are mainly mediated by mechanisms that are gender dimorphic in the substrates they employ. In other words, Toxoplasma gondii is able to manipulate the behaviour of female rats. However, the mechanism underlying this behaviour is gender dimorphic in the substrates involved. Taken together, this forms one more example of the need to factor in gender as a biological variable when designing experiments and interpreting results.